Laser irradiation and pomegranate peel for preservation of the strawberry quality - N. Elsayed; H. Elkashef; Sh. R. Ali (Пищевые системы)
The present study is aimed to explore the influence of laser irradiation and coating with chitosan and pomegranate peel extract on the physico-chemical properties, weight loss, firmness, functional, microbiological, color, and sensory characteristics of strawberry for fifteen days of cold storage. Four treatments of strawberry were conducted with laser irradiation for 6 min. The second, third, and fourth groups were coated with chitosan, pomegranate peel extract (PPE), and mixture of chitosan and PPE at ratio 1:1. Compared to untreated strawberries, the exposure to laser radiation decreased the weight loss of strawberries by 43.44%. Also, the laser irradiation reduced the negative effect of storage on the total phenolic content, anthocyanin, ascorbic acid, and antioxidant ability of strawberry. The exposure of strawberry to laser irradiation reduced the counts of fungi and psychrotrophic bacteria and provided the positive effect on the color and sensory attributes. The coating with PPE and chitosan enhanced the positive effect of laser irradiation on the functional and quality properties of strawberry during its cold storage. It can be concluded that laser irradiation and coating with PPE may be applied as novel techniques for the preservation of strawberry properties during its storage period.